BDNF Val66Met genotype modulates the effect of childhood adversity on subgenual anterior cingulate cortex volume in healthy subjects - Gerritsen, L; Tendolkar, I; Franke, B; Vasquez, A A; Kooijman, S; Buitelaar, J; Fernández, G; Rijpkema, M (Molecular psychiatry, 2012)
According to the neurotrophic hypothesis of depression, stress can lead to brain atrophy by modifying brain-derived neurotrophic factor (BDNF) levels. Given that BDNF secretion is affected by a common polymorphism (rs6265, Val66Met), which also is associated with depression, we investigated whether this polymorphism modifies the effect of childhood adversity (CA) on local gray matter (GM) volume in depression-relevant brain regions, using data from two large cohorts of healthy subjects. We included 568 healthy volunteers (aged 18–50 years, 63% female) in our study, for whom complete data were available, with magnetic resonance imaging data at 1.5 Tesla ( N =275) or 3 Tesla ( N =293). We used a whole brain optimized voxel-based morphometry (VBM) approach assessing genotype-dependent GM differences, with focus on the amygdala, hippocampus and medial prefrontal cortex (PFC; including anterior cingulate cortex (ACC) and orbitomedial PFC). CA was assessed using a validated questionnaire. In both cohorts, we found that BDNF methionine (Met)-allele carriers with a history of CA had significantly less GM in subgenual ACC ( P <0.05) compared with Met-allele carriers without CA and Val/Val homozygotes with CA. No differences were found in hippocampus, amygdala and orbitomedial PFC. On the basis of our findings, we conclude that BDNF Met-allele carriers are particularly sensitive to CA. Given the key role of the subgenual ACC in emotion regulation, this finding provides an important mechanistic link between stress and BDNF on one hand and mood impairments on the other hand.